2011
DOI: 10.1021/cr100403z
|View full text |Cite
|
Sign up to set email alerts
|

Update 1 of: Synthesis and Functionalization of Indoles Through Palladium-Catalyzed Reactions

Abstract: |Chem. Rev. 2011, 111, PR215-PR283Chemical Reviews REVIEW Finally, one can reasonably anticipate that future studies will provide new applications to the preparation of complex molecules, particularly in the area of biologically active compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
167
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(171 citation statements)
references
References 592 publications
2
167
0
Order By: Relevance
“…C-H bonds of electron-rich aromatic amides showed better activity [102]. Chatani and co-workers found that utilizing a bidentate system, aromatic amides having a pyridin-2-ylmethylamine moiety could undergo cyclocarbonylation through C-H bond activation in the presence of catalytic amount of Ru 3 (CO) 12 and CO (Scheme 34b). Phthalimides were obtained in moderate to good yields.…”
Section: Synthesis Of Five-membered Heterocycles Via Oxidative Carbonmentioning
confidence: 99%
“…C-H bonds of electron-rich aromatic amides showed better activity [102]. Chatani and co-workers found that utilizing a bidentate system, aromatic amides having a pyridin-2-ylmethylamine moiety could undergo cyclocarbonylation through C-H bond activation in the presence of catalytic amount of Ru 3 (CO) 12 and CO (Scheme 34b). Phthalimides were obtained in moderate to good yields.…”
Section: Synthesis Of Five-membered Heterocycles Via Oxidative Carbonmentioning
confidence: 99%
“…There are various synthetic routes for the preparation of indole derivatives, such as Fischer indole synthesis [32], Bartoli indole synthesis [31] or Pd/Cu-catalyzed cyclization [42,43]. Previously, we reported the preparation of indole bearing pendant functionalities using the Sonogashira reaction followed by Zn-mediated cyclization [28].…”
Section: Preparations Of Ligand Precursors and Magnesium Complexesmentioning
confidence: 99%
“…In this context, palladium catalysis has revolutionized modern indole synthesis, with the vast majority of now-established synthetic protocols involving assembly of the pyrrole ring fragment by use of combinations of nitrogen nucleophiles and alkyne synthons. [8][9][10] Notwithstanding the utility of such methods, the development of efficient new routes to indoles that make use of alternative disconnection strategies and source materials remains an important goal in the quest to diversify inroads to these important heterocycles. Of particular interest are new syntheses that accommodate inexpensive and structurally variable substrate classes within one-pot, multicomponent reactions, [11,12] ideally without the requirement of inert atmosphere reaction conditions.…”
Section: Introductionmentioning
confidence: 99%